The architectural template method: templating architectural knowledge to efficiently conduct quality‐of‐service analyses. (25th August 2017) - Lehrig, Sebastian; Hilbrich, Marcus; Becker, Steffen
Summary: Software architects plan the realization of software systems by assessing design decisions on the basis of architectural models. Using these models as input, architectural analyses assess the impact of architects' decisions on quality‐of‐service properties. While the creation of suitable architectural models requires software architects to apply complex architectural knowledge, for example, in the form of established architectural styles and patterns, current architectural analyses lack support for directly reusing such knowledge. This lack points to an unused potential to make the work of software architects more effective and efficient. To use this potential, we introduce the architectural template (AT) method, an engineering method that makes design‐time analyses of quality‐of‐service properties of software systems more efficient. The AT method allows to quantify quality‐of‐service properties on the basis of reusable modeling templates that capture recurring architectural knowledge. Architects just need to customize such templates with system‐specific parts. In a case study, we illustrate the applicability of the AT method in the domains of distributed and cloud computing and its suitability for the quality‐of‐service properties performance, scalability, elasticity, and cost‐efficiency. Copyright © 2017 John Wiley & Sons, Ltd.